"Verstoßt den Bösen aus eurer Mitte!" (1 Kor 5,13): der Umgang mit den "Bösen" im Alltag der Versammlung Gottes in Korinth - Zimmermann, Christiane (Zeitschrift für Theologie und Kirche, 2025)
The article explores the question of how the presence of evil (poneros) actors was addressed in the early Christian community of Corinth. Drawing on the doctrine of fundamental salvation for believers and acknowledging their presence in the evil aion, Paul crafts an apotropaic formula against the enemies of Christ in 1 Corinthians 16:22. Concurrently, in 1 Corinthians 5:1 - 13, Paul provides the Corinthians with instructions on how to address a currently evil individual, with the objective of returning the evil to the evil aion.